2018
DOI: 10.1371/journal.pone.0199699
|View full text |Cite
|
Sign up to set email alerts
|

CHIP E3 ligase mediates proteasomal degradation of the proliferation regulatory protein ALDH1L1 during the transition of NIH3T3 fibroblasts from G0/G1 to S-phase

Abstract: ALDH1L1 is a folate-metabolizing enzyme abundant in liver and several other tissues. In human cancers and cell lines derived from malignant tumors, the ALDH1L1 gene is commonly silenced through the promoter methylation. It was suggested that ALDH1L1 limits proliferation capacity of the cell and thus functions as putative tumor suppressor. In contrast to cancer cells, mouse cell lines NIH3T3 and AML12 do express the ALDH1L1 protein. In the present study, we show that the levels of ALDH1L1 in these cell lines fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 62 publications
3
18
0
Order By: Relevance
“…However, the effect of ALDH1L1 on purine biosynthesis would be crucial for rapidly proliferating cells but not quiescent cells. This is in agreement with the phenomenon that the ALDH1L1 expression is down-regulated in S-phase of the cell cycle but not in quiescent cells 14 . In the liver, overwhelming majority of cells are in non-proliferating state 51 , which would explain the lack of the effect of the Aldh1l1 KO on purine pools, and this is also in agreement with the 10-formyl-THF accumulation (otherwise 10-formyl-THF would be taken up by the purine biosynthesis).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the effect of ALDH1L1 on purine biosynthesis would be crucial for rapidly proliferating cells but not quiescent cells. This is in agreement with the phenomenon that the ALDH1L1 expression is down-regulated in S-phase of the cell cycle but not in quiescent cells 14 . In the liver, overwhelming majority of cells are in non-proliferating state 51 , which would explain the lack of the effect of the Aldh1l1 KO on purine pools, and this is also in agreement with the 10-formyl-THF accumulation (otherwise 10-formyl-THF would be taken up by the purine biosynthesis).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the enzyme clears one-carbon groups, in the form of CO 2 , from the folate pool which might limit the overall biosynthetic capacity of folate-dependent reactions thus playing a regulatory role 11,13 . In support of such proliferation regulatory role, we have recently shown that ALDH1L1 is down-regulated in S-phase of the cell cycle in NIH 3T3 cells 14 . Several studies also implicated ALDH1L1 as a folate depot, the function likely important for preventing folate degradation 1517 .…”
Section: Introductionmentioning
confidence: 79%
“…Of note, our previous work implicated CerS6 and C 16 -ceramide elevation in the cellular response to folate stress 11 . Similar to serum starvation experiments, p53 pulled down from cells experiencing folate stress (due to elevation of the folate-stress enzyme ALDH1L1 11 , 27 ) had high levels of bound C 16 -ceramide as well (Supplementary Figure 12 ).
Fig.
…”
Section: Resultsmentioning
confidence: 74%
“…It is not clear whether these enzymes have overlapping metabolic functions or whether each reaction serves different purposes. ALDH1L1 is suggested as a regulator of the folate metabolism, the function closely associated with the regulation of cellular proliferation [ 10 , 11 , 13 ]. In agreement with such function, ALDH1L1 is strongly and ubiquitously downregulated in many human cancers through the promoter methylation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Merging a folate-binding domain with the aldehyde dehydrogenase catalytic machinery enabled a novel enzymatic reaction, the oxidation of folate-bound formyl group to CO 2 . Experimental data suggest that this reaction is important for the regulation of the overall cellular folate pool as well as the proliferative capacity of the cell [ 10 , 11 ]. We have recently generated mice with targeted Aldh1l1 knockout and demonstrated that the animals lacking the enzyme display metabolic signs of folate deficiency and have impaired glycine metabolism in the liver [ 12 ].…”
Section: Introductionmentioning
confidence: 99%